Elastic behaviour at the nanoscale of innovative composites of nanoporous gold and polymer. (November 2017) - Griffiths, Emma; Bargmann, Swantje; Reddy, B.D.
Abstract: Nanoporous gold is a material with unique properties that make it attractive for use in multiple areas. It has an extremely high compressive strain capability but is very brittle in tension which limits its usage. One means of addressing this limitation is to fill the voids of the nanoporous material with a polymer, resulting in a more ductile and stronger material. In this work, the mechanical properties of a nanocomposite representative sample are studied numerically. The study is based on homogenization with the use of three types of boundary conditions. The stress–strain response within the composite is also analysed. Under a pure compression test, the sample shows both compressive and tensile strains and stresses. This is due to the complex interaction within the microstructure. Within the composite, the polymer is still considerably more compliant than the gold material showing much higher strains. The resultant forces, moments and torques acting on representative ligament cross-sections are also investigated under compressive loading. Bending moments and normal forces dominate the modes of loading. Ligaments along the compression axis show markedly higher normal forces compared to ligaments perpendicular to this axis. The normal stress distributions of the ligaments show clear trends towards combined bending and normal forces while there is no discernible pattern to the shear stress distributions. These nevertheless generate high shear forces and torques.